REVOLUSI DALAM PAKAN, PROBIOTIK MENINGKATKAN PRODUKTIVITAS SAPI POTONG: Review - Nugroho, Irfan Aji; Ashodhiqoh, Rahmi Ma’rufah; danang nugroho aji; Hidayat, Nova Fahrizal; Rahayu, Tri Puji (JURNAL PETERNAKAN SABANA, 2025)
Productivity, especially feed efficiency and average daily gain (ADG), is the main focus in the beef cattle farming industry. Antibiotics emerged as an innovation that addressed various issues including feed efficiency and ADG, but were limited due to concerns regarding the negative impacts of their use. Probiotics are an alternative that has emerged to replace the use of antibiotic feed. Probiotics can help improve the quality of digestion, help fermentation including rumen microbial activity, nutrient absorption, and livestock health. Providing microbes has a real impact on increasing ADG, but has various challenges such as inadequate human resources, shelf life of probiotics, and appropriate methods of use. The use of probiotics is a good consideration in the beef cattle farming industry, apart from not having a negative impact like antibiotics, probiotics still provide good results in the productivity of beef cattle including ADG